2013
DOI: 10.1111/jonm.12162
|View full text |Cite
|
Sign up to set email alerts
|

The changing skill mix in nursing: considerations for and against different levels of nurse

Abstract: When evaluating nursing skill mix, a higher percentage of registered nurses may result in health-care facility cost savings by providing a shorter length of stay and decreased patient complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 29 publications
0
71
0
1
Order By: Relevance
“…[5,22,23] The sample of participants was drawn from five clinical medical/surgical units in three separate locations in rural New South Wales Australia. Nursing staff included registered nurses, enrolled nurse, assistants in nursing, nurse unit managers and clinical (ward based) nurse educators.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…[5,22,23] The sample of participants was drawn from five clinical medical/surgical units in three separate locations in rural New South Wales Australia. Nursing staff included registered nurses, enrolled nurse, assistants in nursing, nurse unit managers and clinical (ward based) nurse educators.…”
Section: Methodsmentioning
confidence: 99%
“…[1,2] In Australia, registered nurses find themselves in a position of supervising other registered (including new graduate) and enrolled Nurses [3][4][5] as well as other unregulated and non-credentialed health care workers. [5][6][7] In order to manage the increased demands of responsibility and supervision of this range of varied staff classifications, team nursing as a model of care was introduced in five clini-cal units medical/surgical in a rural region in Australia as a way to address this varied skill mix. A team nursing model of care in this context refers to all levels of nurses who contributed to the direct nursing care (NC) of patients including registered and unregistered staff.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of financial resources in health care institutions is reflected by reduced spending on these professionals, reflecting on the quality of care provided to the population (5) . Studies have shown better results where the ratio between nurses and patients is adequate (5)(6)(7) , including reduced mortality and customer satisfaction. The situation of emergency services is worrisome because its features, such as fluctuating demand and occupancy rate, complicate the choice of an instrument for the measuring of nursing human resourses in this area (8) .…”
Section: Introductionmentioning
confidence: 99%